SOCIALIZATION TO YOUTH ABOUT THE DEVELOPMENT OF INFORMATION AND COMMUNICATION TECHNOLOGY - Masriani Situmorang; Mulyana Mulyana; Veggy Veggy (Universitas Muhammadiyah Mataram, 2021)
Abstrak: Peningkatan inovasi data dan korespondensi telah mengubah cara orang berkomunikasi dengan orang lain. Web berubah menjadi ruang canggih lain yang membuat ruang sosial. Tidak dapat dipungkiri bahwa kehadiran web memberikan banyak kemudahan bagi para kliennya. Berbagai akses ke data dan pengalihan dari mana saja di dunia dapat dilihat melalui web. Web memasuki batas elemen kehidupan, waktu, dan ruang klien, yang dapat diakses oleh siapa saja, kapan saja, dan di mana saja. Motivasi di balik administrasi wilayah lokal ini adalah untuk mempengaruhi kehidupan individu dengan lebih baik. Strategi yang digunakan dalam latihan augmentasi dilakukan dengan empat macam, lebih spesifiknya: teknik sapaan, percakapan, tanya jawab dan survei. Perubahan inovasi dari yang mudah menjadi mutakhir dapat dikatakan sebagai jenis modernisasi yang biasanya juga akan diikuti oleh modernisasi (pemikiran). Hasil kegiatan pengabdian masyarakat ini cukup berdampak positif bagi remaja khususnya yang ada di panti Asuhan Rizki Ilahi. Kegiatan pengabdian masyarakat yang sudah dilakukan berjalan sangat baik dimana selama kegiatan ini berlangsung, terjadi perubahan perilaku berfikir pada remaja yang ada di panti asuhan Rizki Ilahi terkait pemanfaatan sistem informasi dan komunikasi. Abstract: The development of information and communication technology has changed the way individuals interact with other individuals. The internet is becoming a new digital space that creates a cultural space. It is inevitable that the existence of the internet provides a lot of convenience to its users. Various access to information and entertainment from various parts of the world can be searched via the internet. The internet penetrates the boundaries of the dimensions of the user's life, time and space, which can be accessed by anyone, anytime, anywhere. The purpose of this community service is to have a better impact on people's lives. The method used in extension activities is carried out in four types, namely: lecture method, discussion, question and answer and questionnaire. Changes in technology from simple to advanced can be said to be a form of modernization which usually will also be followed by the modernization of ideas (ideas). The results of this community service activity had quite a positive impact on adolescents, especially those at the Rizki Ilahi orphanage. Community service activities that have been carried out have gone very well where during this activity, there has been a change in thinking behavior among teenagers in the Rizki Ilahi orphanage regarding the use of information and communication systems.